Tuntunan Islam=min taujihat islam - Syaikh Mahmoud Syaltout (Bulan Bintang, 1973)
Oen, Jil.I=c.1-2; Jil.II=c.1-4; Jil. III=c.1-5 Jil. IV=c.1-4 Jil.V=c.1/ir,jil.IV,c.5 /ir, jil.1,c.3/wk, jl.2 c.5/en, jil.2=c.6/tr, jil.3=c.6/en, jil.1=c.4/